Characterization and biomedical application of phytosynthesized gold nanoparticles from Datura stramonium seed extract. Issue 1 (March 2020) - Oladipo, IC; Lateef, A; Azeez, MA; Asafa, TB; Yekeen, TA; Ogunsona, SB; Irshad, HM; Abbas, SH
Abstract: This study describes characterization and some biological evaluation of gold nanoparticles synthesized using aqueous seed extract of Datura stramonium . The phytosynthesized AuNPs was characterized by UV-Vis spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), Energy Dispersive X-ray (EDX) and Scanning Electron Microscopy (SEM) and evaluated for antifungal, antioxidant, thrombolytic and anticoagulant activities. The AuNPs were nearly spherical, and agglomerated in nature with size ranges of 75.1-156.5 nm. Gold was the most occurring metal noted on EDX analysis, while the AuNPs showed face-centred crystalline pattern. The UV-visible spectrum of the AuNPs synthesized displayed clear peak at 536 nm. The FTIR peaks at 3423.76, 2920.32, 2360.95 and 1635.69 cm −1 attributed to the involvement of proteins in the AuNPs biofabrication and capping. The AuNPs showed potent antifungal activity through inhibitions of mycelia by 57.9, 60.7, 64.5, 69.6 and 80.6 % against Fusarium solani, Candida albicans, Aspergillus niger, A. flavus and A. fumigatus at 250 μg/ml respectively. The AuNPs synthesized showed scavenging properties of 28.9, 37.3, 42.5 and 52.4 % at 250, 500, 750 and 1000 μg/ml against 2, 2-diphenyl-1-picrylhydrazyl. Furthermore, the synthesized AuNPs also showed free radical scavenging properties against nitric oxide at 250 (52.20 %), 500 (55.73 %), 750 (56.71 %) and 1000 (59.51 %) μg/ml respectively using sodium nitroprusside as positive control. Blood coagulation was prevented by the AuNPs at 250 (54 %), 500 (55 %), 750 (56 %) and 1000 (59 %) μg/ml. Also, AuNPs showed thrombolytic potential by causing lysis of blood clot thus, showing potential for biomedical applications. An in-expensive and environmental-friendly synthesis of AuNPs from Datura stramonium seed has been presented for various nano-biotechnological applications.